An ergonomic comfort workspace analysis of master manipulator for robotic laparoscopic surgery with motion scaled teleoperation system. Issue 6 (31st August 2022) - Kang, DongHoon; Kwon, Dong‐Soo
Abstract: Background: In robotic surgery, a surgeon controls a surgical robot through a master manipulator in motion scaled teleoperation environment. However, there are no clear criteria for the master's workspace. Methods: From the user experiment, we proposed an Ergonomic Comfort Workspace considering ergonomics and performed a verification experiment using the actual surgeons' dataset. Results: From the user experiment, with comfortable posture, there was no significant difference ( p ‐value < 0.05) between the master workspace when the task space is increased, and the workspace is defined as an ergonomic comfort workspace. Using the JIGSAWS dataset, elementary surgical tasks using surgical robots, verify the effectiveness of the ergonomic comfort workspace (ECW). It was confirmed that more than 95% of surgical task data were almost included in the ECW. Conclusions: The proposed ECW of the master for robotic laparoscopic surgery enables surgeons to perform surgery with high comfort and precision.